Cell-Specific mRNA Profiling of the Caenorhabditis elegans Somatic Gonadal Precursor Cells Identifies Suites of Sex-Biased and Gonad-Enriched Transcripts. Issue 12 (1st December 2015) - Kroetz, Mary B; Zarkower, David
Abstract: The Caenorhabditis elegans somatic gonad differs greatly between the two sexes in its pattern of cell divisions, migration, and differentiation. Despite decades of study, the genetic pathways directing early gonadal development and establishing sexual dimorphism in the gonad remain largely unknown. To help define the genetic networks that regulate gonadal development, we employed cell-specific RNA-seq. We identified transcripts present in the somatic gonadal precursor cells and their daughter cells of each sex at the onset of sexual differentiation. We identified several hundred gonad-enriched transcripts, including the majority of known regulators of early gonadal development, and transgenic reporter analysis confirmed the effectiveness of this approach. Before the division of the somatic gonad precursors, few sex-biased gonadal transcripts were detectable; less than 6 hr later, after their division, we identified more than 250 sex-biased transcripts, of which about a third were enriched in the somatic gonad compared to the whole animal. This indicates that a robust sex-biased developmental program, some of it gonad-specific, initiates in the somatic gonadal precursor cells around the time of their first division. About 10% of male-biased transcripts had orthologs with male-biased expression in the early mouse gonad, suggesting possible conservation of gonad sex differentiation. Cell-specific analysis also identified approximately 70 previously unannotated mRNA isoforms that are enriched in the somatic gonad. Our data illustrate the power of cell-specific transcriptome analysis and suggest that early sex differentiation in the gonad is controlled by a relatively small suite of differentially expressed genes, even after dimorphism has become apparent.